Determination of the Influence of Fuel Switching Regulation on the Sulfur Dioxide Content of Air in a Port Area Using DID Model - Fan Zhou; Yunli Fan (Advances in Meteorology)
Since January 1, 2018, ships berthed at all ports of the three designated emission control areas (ECAs) in China are required to use fuel with sulfur content not exceeding 0.5% (m/m), excluding one hour postarrival and one hour predeparture. To understand changes in SO2 due to this policy, two observation stations were established on Waigaoqiao Dock in the Yangtze River estuary. Three data types were collected from March 2018 to May 2018, namely, wind speed and direction, SO2 concentration, and ships’ arrival and departure times. The statistics indicate that the wind direction changed little during the observation period and SO2 concentration was below 5 µg/m3 77.47% of the time. Meanwhile, ships’ arrival and departure at the dock had a distinct influence on overall SO2 distribution, including occurrence of concentrations ≥5 µg/m3. The three types of data were divided into six groups and a difference-in-difference model was used for analysis. The result shows that SO2 concentration increases due to the use of high-sulfur fuel and is especially significant when the wind is southwesterly. Furthermore, there was a positive correlation between increases in SO2 concentrations over 5 µg/m3 and the number of ships arriving or departing from the port. This study reports the positive impact of fuel switching on air quality and can be used to evaluate adherence to the ECA policy.